"I'm Not Leaving, I'm Not Afraid": (Re)Visiting the Dysfunctional Systems of Justice on Gender-based Violence (GBV) in Uganda. Issue 1 (2nd January 2016) - Bamidele, Oluwaseun
ABSTRACT: The narratives on many of the gruesome African post–civil wars have always acknowledged the evil that the females were subjected to. In Uganda, women were both victims and weapons of war. Despite the fact that Uganda's justice system adopted the Truth and Reconciliation Commission (TRC) to prosecute gender-based violence (GBV) as a national crime, rape continues to be a weapon of war. As a result, there are traditional and contemporary barriers to access gender-based justice in many African states, including Uganda. Issues regarding GBV including sexual assault justice in post–civil war society has remained very sensitive. Beyond the fact that it may lead to stigmatization, the social deficit of this is yet to be deconstructed in Uganda. The dysfunctional systems of justice process cannot be seen as agency of reward. This system is usually expensive to service and maintain. This is coupled with the loss of faith syndrome in judicial systems by the GBV victims. As a combination of weak judicial systems and social and economic impediment limit the prospects of a GBV, this study assesses gender justice in the post-civil war Uganda. It focuses on Uganda for a variety of reasons, among which is that Uganda is the first African state to adopt TRC in 1974, and, from a gender perspective, the 1995 Constitution of the Republic of Uganda is acclaimed as being one of the only two gender-sensitive constitutions in Africa. This study has broader implications, as it raises questions about the relevance of the regime of justice on the victims and the perpetrator and draw lessons from this experience.